Bioeconomic Analysis of Pelagic Fish Resources in Bangka Waters Landed at PPN Sungailiat - Monischa Br Sebayang; Ni luh Eta Yuspita; Valentin Vina Ratnapuri; Misri Yandi; Wika Noventa (Jurnal Perikanan dan Kelautan, 2026)
Bangka Belitung Islands are an archipelago with a water area (65,301 km²) four times larger than its land area. This area has fishery resources that have great potential to support the economy, This study aims to analyze the bioeconomics of pelagic fish resources in Bangka waters landed at Sungailiat Nusantara Fishing Port using a surplus production approach. The research was conducted in January 2025 at PPN Sungailiat, Bangka Regency, Bangka Belitung Islands. Data were collected using descriptive methods and analyzed using the Schaefer surplus production model from January to March 2025. The results showed that the Maximum Sustainable Yield (MSY) was 6005.948 tons/year. From 2019 to 2024, catch production remained below the MSY, indicating potential for optimization. The optimum fishing effort was 5914 trips/year, with 2019–2021 exceeding this level, while 2022–2024 remained below it. These findings suggest that pelagic fisheries management can still be improved by emphasizing sustainability and economic efficiency. It is recommended that resource management policies target fishing efforts approaching the Maximum Economic Yield (MEY) to achieve a balance between catch quantity and economic profit.